Mouse molecular genetics - Wassarman, Paul M. (Guide to techniques in mouse development, 2010)
This volume comprehensively covers new technologies and methodologies that have appeared for the study of mouse development. This volume is Part B of an update of volume 225, Guide to Techniques in Mouse Development, edited by P.M. Wassarman and M.L. DePamphilis and published in 1993. Comprehensively covers new techniques for the cryopreservation of gametes and embryos, production of transgenic and null (knockout) animals (use of ES cells), generation of conditional/inducible mutant animals, use of gene-trap